Preparation method of nickel mesh loaded efficient urea assisted hydrogen production system catalyst
By loading high-efficiency urea on nickel network to assist in the preparation of hydrogen production system catalyst, the problems of slow urea electrolysis reaction rate and high catalyst stability requirements are solved, the activity and stability of the catalyst electrode are improved, and hydrogen energy production and wastewater resource utilization are promoted.
Patent Information
- Application Number
- CN202411966369.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
The kinetics of urea electrolytic reactions are complex, the reaction rate is slow, and the selectivity and stability of the catalyst are high, which leads to the development of efficient and stable urea electrolytic catalysts becoming a key technical challenge.
The preparation method of a catalyst for hydrogen production system is used to assist in the preparation of nickel-mounted high-efficiency urea, including nickel substrate pretreatment, preparation of activated electrolyte and electrochemical activation, and the activity and stability of the catalyst electrode are improved through these steps.
It improves the activity performance and stability of the catalyst electrode, enhances the efficiency and effectiveness of urea-coupled hydrogen production, provides a new hydrogen energy production solution, and promotes wastewater treatment and resource utilization.
Smart Images

Figure CN119710777A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of urea-coupled hydrogen production, and in particular to a method for preparing a catalyst for a hydrogen production system in which high-efficiency urea is loaded on a nickel mesh and assisted. Background Art
[0002] Developing clean and efficient hydrogen production technology is one of the important ways to solve the energy crisis. Traditional water electrolysis hydrogen production technology is limited by its high energy consumption and cost, which limits its large-scale application. Therefore, exploring low-energy and high-efficiency hydrogen production methods has become a research hotspot. In this context, urea-assisted electrolysis hydrogen production technology has attracted much attention because it can simultaneously achieve waste resource utilization and low-cost hydrogen production.
[0003] Urea is a common nitrogen-containing organic compound that is widely present in industrial and agricultural wastewater. Its high-concentration discharge not only pollutes the environment, but also causes ecological problems such as eutrophication of water bodies. Through the urea electrolysis reaction (UreaOxidation Reaction, UOR), urea is decomposed into harmless nitrogen and carbon dioxide, while significantly reducing the energy consumption of hydrogen production by electrolysis of water. This method can not only effectively treat urea-containing wastewater and realize the resource utilization of waste, but also reduce the energy demand of the hydrogen production process, with significant environmental and economic benefits.
[0004] However, the kinetics of urea electrolysis reaction is relatively complex, involving multiple electron transfer processes, slow reaction rate, and high requirements for catalyst selectivity and stability. Therefore, the development of efficient and stable urea electrolysis catalysts has become a key technical challenge in this field. Summary of the invention
[0005] In order to solve the above technical problems, a technical solution adopted by the present invention is: Provided is a method for preparing a catalyst for a hydrogen production system supported by high-efficiency urea on a nickel mesh, the steps comprising: (1) Nickel substrate pretreatment: Activate the nickel substrate to remove grease and oxide layers on the nickel substrate; (2) Preparation of an activated electrolyte: Sodium hypophosphite, an alkaline substance and 30-200 mL of deionized water are mixed and ultrasonically treated to completely dissolve the mixture to obtain an activated electrolyte, wherein the concentration of sodium hypophosphite in the activated electrolyte is 0.05-1 mol / L and the concentration of the alkaline substance is 0.1-6 mol / L; wherein the alkaline substance includes sodium hydroxide or potassium hydroxide; (3) Electrochemical activation: The electrochemical activation process is carried out in a two-electrode or three-electrode system. The pretreated nickel substrate is used as the anode and cathode and immersed in the activation electrolyte. The applied activation potential is 0.5~4.5V, the potential increase gradient is 0.1~0.5V, and the single potential activation time is 0.5~120min. The electro-activated anode is removed, rinsed, and dried as a catalyst electrode.
[0006] In a preferred embodiment of the present invention, the pretreatment step includes: taking 0.2g of polysorbate-80 and 1g of potassium hydroxide and dissolving them in 10-50mL of deionized water, heating the solution to 80-95°C to completely dissolve the solid matter; immersing the nickel substrate in the solution and soaking it for 120 minutes to remove grease on the surface; then taking out the nickel substrate and rinsing it with deionized water for 5 times; placing the nickel substrate in a vacuum drying oven and drying it at 60°C.
[0007] In a preferred embodiment of the present invention, the nickel substrate includes one of a nickel mesh, nickel foam, and a nickel plate.
[0008] In a preferred embodiment of the present invention, the concentration of sodium hypophosphite is 0.5 mol / L.
[0009] In a preferred embodiment of the present invention, the concentration of the sodium hydroxide solution is 1 mol / L.
[0010] In a preferred embodiment of the present invention, the ultrasonic time is 20 to 50 minutes.
[0011] A catalyst electrode for a nickel mesh-loaded high-efficiency urea-assisted hydrogen production system is prepared by any of the above methods.
[0012] The beneficial effects of the present invention are: not only the activity performance and stability of the catalyst electrode are improved, but also the preparation efficiency of the catalyst electrode is improved, thereby improving the high efficiency and effectiveness of urea-coupled hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work, among which: Figure 1 is a metallographic microscope spectrum of the nickel substrate before electrochemical activation of the present invention; Figure 2 is a metallographic microscope spectrum of the catalyst electrode after electrochemical activation of the present invention; Figure 3It is a comparison diagram of the UOR performance curves of the nickel-based catalyst before and after activation and modification in Example 1 of the present invention; Figure 4 is a comparison diagram of HER performance curves before and after activation modification in Example 1 of the present invention; Figure 5 3 is a time-voltage curve of the catalyst electrode in Example 1 of the present invention. DETAILED DESCRIPTION
[0014] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0015] See also Figure 1-5 , the embodiment of the present invention includes: A method for preparing a catalyst for a hydrogen production system supported by high-efficiency urea on a nickel mesh, the steps comprising: (1) Nickel substrate pretreatment: The nickel substrate is activated and pretreated to remove grease and oxide layers on the nickel substrate.
[0016] Further preferably, 0.2 g of polysorbate-80 and 1 g of potassium hydroxide are dissolved in 10-50 mL of deionized water, and the solution is heated to 80-95 °C to completely dissolve the solid matter; the nickel substrate is immersed in the solution and soaked for 120 min to remove grease on the surface; the nickel substrate is then taken out and rinsed with deionized water for 5 times; the nickel substrate is placed in a vacuum drying oven and dried at 60 °C.
[0017] Preferably, the pretreated nickel substrate is cut into a certain size for later use. For example, the nickel mesh can be 1 cm 2 of mesh.
[0018] Further preferably, the nickel substrate includes one of a nickel mesh, nickel foam, and a nickel plate.
[0019] (2) Preparation of activated electrolyte: Sodium hypophosphite and alkaline substance in a certain molar ratio are mixed with 30-200 mL of deionized water, and ultrasonicated for a certain period of time to completely dissolve them to obtain an activated electrolyte. The concentration of sodium hypophosphite in the activated electrolyte is 0.05-1 mol / L, and the concentration of the alkaline substance is 0.1-6 mol / L.
[0020] More preferably, the concentration of sodium hypophosphite is 0.05-1 mol / L.
[0021] More preferably, the alkali solution can be a sodium hydroxide solution or a potassium hydroxide solution.
[0022] Further preferably, the ultrasonic time should be controlled within 20 to 50 minutes.
[0023] (3) Electrochemical activation: The electrochemical activation process is carried out in a two-electrode or three-electrode system. The pretreated nickel substrate is used as the anode and cathode and immersed in the activation electrolyte. The applied activation potential is 0.5~4.5V, the potential increase gradient is 0.1~0.5V, and the single potential activation time is 0.5~120min. The electro-activated anode is removed, rinsed, and dried as a catalyst electrode.
[0024] (4) The prepared catalyst electrode was placed in an electrolyte mixed solution of 1 M KOH and 0.33 M urea to test its urea-coupled hydrogen production catalytic performance. Example
[0025] The nickel mesh substrate was sandblasted on both sides (90 mesh white corundum sandblasting), and then the nickel mesh substrate was treated and soaked in a mixed solution of 0.2g polysorbate-80 and 1g potassium hydroxide at 60°C for 2h for pretreatment, and then cut into 1*1cm nickel mesh for use; 40ml of activation electrolyte was prepared by mixing KOH, sodium hypophosphite and deionized water, and the concentrations of KOH and sodium hypophosphite in the activation electrolyte were 1M and 0.1M, respectively; the pretreated nickel mesh was used as a working electrode and a counter electrode to form a two-electrode system, and a 0.5~3V step potential activation was applied, the potential increment gradient was 0.2V, and the single potential activation time was 10min to obtain a catalyst electrode; after electrochemical activation, the catalyst electrode was rinsed with deionized water and then dried.
[0026] A three-electrode system was constructed with the dried catalyst electrode as the working electrode, the Pt sheet electrode as the counter electrode, and the Hg / HgO electrode as the reference electrode. The LSV curves of the hydrogen evolution reaction and the urea oxidation reaction were tested in 1 M KOH and 0.33 M urea aqueous solutions. Example
[0027] The nickel mesh substrate was double-sided sandblasted (90 mesh white corundum sandblasting), and then the nickel mesh substrate was treated and soaked in a mixed solution of 0.2g polysorbate-80 and 1g potassium hydroxide at 60°C for 2h for pretreatment, and then cut into 1*1cm nickel mesh for use; 40ml of activation electrolyte was prepared by mixing KOH, sodium hypophosphite and deionized water, and the concentrations of KOH and sodium hypophosphite in the activation electrolyte were 1M and 0.5M, respectively; the pretreated nickel mesh was used as a working electrode and a counter electrode and placed in the activation electrolyte to form a two-electrode system, and a 0.5~3V step potential activation was applied, the potential increment gradient was 0.2V, and the single potential activation time was 10min to obtain a catalyst electrode, and after electrochemical activation, the catalyst electrode was rinsed with deionized water and dried.
[0028] A three-electrode system was constructed with the dried catalyst electrode as the working electrode, the Pt sheet electrode as the counter electrode, and the Hg / HgO electrode as the reference electrode. The LSV curves of the hydrogen evolution reaction and the urea oxidation reaction were tested in 1 M KOH solution + 0.33 M urea aqueous solution. Example
[0029] The nickel mesh substrate was double-sided sandblasted (90 mesh white corundum sandblasting), and then the nickel mesh substrate was treated and soaked in a mixed solution of 0.2g polysorbate-80 and 1g potassium hydroxide at 60°C for 2h for pretreatment, and then cut into 1*1cm nickel mesh for use; 40ml of activation electrolyte was prepared by mixing KOH, sodium hypophosphite and deionized water, and the concentrations of KOH and sodium hypophosphite in the activation electrolyte were 6M and 0.1M, respectively; the pretreated nickel mesh was placed in the activation electrolyte as a working electrode and a counter electrode to form a two-electrode system, and a 0.5~3V step potential activation was applied with a potential increase gradient of 0.2V and a single potential activation time of 10min to obtain a catalyst electrode, and after electrochemical activation, the catalyst electrode was rinsed with deionized water and dried.
[0030] A three-electrode system was constructed by using the dried catalyst electrode as the working electrode, the Pt sheet electrode as the counter electrode, and the Hg / HgO electrode as the reference electrode. The LSV curves of the hydrogen evolution reaction and the urea oxidation reaction were tested in 1 M KOH solution and 0.33 M urea aqueous solution. Example
[0031] The nickel mesh substrate was double-sided sandblasted (90 mesh white corundum sandblasting), and then the nickel mesh substrate was treated and soaked in a mixed solution of 0.2g polysorbate-80 and 1g potassium hydroxide at 60°C for 2h for pretreatment, and then cut into 1*1cm nickel mesh sheets for use; 40ml of activation electrolyte was prepared by mixing KOH, sodium hypophosphite and deionized water, and the concentrations of KOH and sodium hypophosphite in the activation electrolyte were 6M and 0.5M, respectively; the pretreated nickel mesh substrate was used as a working electrode and a counter electrode to form a two-electrode system, and a 0.5~3V step potential activation was applied, the potential increment gradient was 0.2V, and the single potential activation time was 10min to obtain a catalyst electrode, and after electrochemical activation, the catalyst electrode was rinsed with deionized water and dried.
[0032] A three-electrode system was constructed by using the dried catalyst electrode as the working electrode, the Pt sheet electrode as the counter electrode, and the Hg / HgO electrode as the reference electrode. The LSV curves of the hydrogen evolution reaction and the urea oxidation reaction were tested in 1 M KOH solution and 0.33 M urea aqueous solution.
[0033] according to Figure 1 and 2 It can be seen that after electrochemical treatment in a phosphorus-containing electrolyte, obvious black matter adhesion appeared on the surface of the nickel mesh, indicating that the activation process of the phosphorus-containing electrolyte has a significant modification effect on the nickel mesh.
[0034] according to Figure 3 It can be seen that the UOR catalytic potential of the catalyst electrode in 1mol / LKOH+0.33mol / L urea solution with a current density of 300mA / cm2 is 1.99V. Compared with before activation, the UOR catalytic performance is improved by 81mV.
[0035] according to Figure 4 It can be seen that the current density of the catalyst electrode in 1mol / LKOH+0.33mol / L urea solution is 300mA / cm 2 The HER voltage is -0.63V, and the HER performance is improved by 120mV compared with before activation.
[0036] according to Figure 4 It can be seen that the catalyst electrode is used as a positive and negative electrode catalyst to construct two electrodes (1*1cm 2 ) system, in which the electrolyte solution is 1mol / LKOH+0.33mol / L urea electrolyte solution and the current density is 300mA / cm 2 A 200-hour stability operation test was carried out under the conditions of . During the test, the electrolyte was replaced every 8 hours to ensure the stability of the urea concentration. The test results showed that no obvious attenuation occurred within 200 hours in Example 1, and the electrode stability was good.
[0037] The beneficial effects of the preparation method of the nickel mesh-loaded high-efficiency urea-assisted hydrogen production system catalyst of the present invention are: not only improving the activity performance and stability of the catalyst electrode used in the urea-coupled hydrogen production system, but also improving the preparation efficiency of the catalyst electrode, providing a new solution for the production of hydrogen energy, and opening up a new direction for wastewater treatment and resource utilization, which has important scientific significance and broad application prospects.
[0038] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a catalyst for a highly efficient urea-assisted hydrogen production system supported on a nickel mesh, characterized in that the steps include: (1) Nickel substrate pretreatment: Activate the nickel substrate to remove grease and oxide layers on the nickel substrate; (2) Preparation of an activated electrolyte: Sodium hypophosphite, an alkaline substance and 30-200 mL of deionized water are mixed and ultrasonically treated to completely dissolve the mixture to obtain an activated electrolyte, wherein the concentration of sodium hypophosphite in the activated electrolyte is 0.05-1 mol / L and the concentration of the alkaline substance is 0.1-6 mol / L; wherein the alkaline substance includes sodium hydroxide or potassium hydroxide; (3) Electrochemical activation: The electrochemical activation process is carried out in a two-electrode or three-electrode system. The pretreated nickel substrate is used as the anode and cathode and immersed in the activation electrolyte. The applied activation potential is 0.5~4.5V, the potential increase gradient is 0.1~0.5V, and the single potential activation time is 0.5~120min. The electro-activated anode is removed, rinsed, and dried as a catalyst electrode.
2. The method for preparing a high-efficiency urea-assisted hydrogen production system catalyst supported on a nickel mesh according to claim 1, characterized in that: The pretreatment steps include: taking 0.2g polysorbate-80 and 1g potassium hydroxide and dissolving them in 10-50mL deionized water, heating the solution to 80-95℃ to completely dissolve the solid matter; immersing the nickel substrate in the solution for 120 minutes to remove the grease on the surface; then taking out the nickel substrate and rinsing it with deionized water for 5 times; placing the nickel substrate in a vacuum drying oven and drying it at 60℃.
3. The method for preparing a high-efficiency urea-assisted hydrogen production system catalyst supported on a nickel mesh according to claim 1, characterized in that: The nickel substrate includes one of a nickel mesh, a nickel foam and a nickel plate.
4. The method for preparing a high-efficiency urea-assisted hydrogen production system catalyst supported on a nickel mesh according to claim 1, characterized in that: The concentration of the sodium hypophosphite is 0.5 mol / L.
5. The method for preparing a high-efficiency urea-assisted hydrogen production system catalyst supported on a nickel mesh according to claim 1, characterized in that: The concentration of sodium hydroxide solution is 1 mol / L.
6. The method for preparing a high-efficiency urea-assisted hydrogen production system catalyst supported on a nickel mesh according to claim 1, characterized in that: The ultrasound time is 20 to 50 minutes.
7. A catalyst electrode for a high-efficiency urea-assisted hydrogen production system supported on a nickel mesh, characterized in that: Prepared by any one of the methods of claims 1-6.